Network pharmacology integrated with experimental validation to elucidate the mechanisms of action of the Guizhi-Gancao Decoction in the treatment of phenylephrine-induced cardiac hypertrophy - Kaijing Yang; Xiaoli Shan; Yang Songru; Mengwei Fu; Pei Zhao; Wei Guo; Ming Xu; Huihua Chen; Rong Lu; Chen Zhang (Pharmaceutical Biology)
Context The mechanisms of Traditional Chinese Medicine (TCM) Guizhi-Gancao Decoction (GGD) remain unknown.Objective This study explores the mechanisms of GGD against cardiac hypertrophy.Materials and methods Network pharmacology analysis was carried out to identify the potential targets of GGD. In vivo experiments, C57BL/6J mice were divided into Con, phenylephrine (PE, 10 mg/kg/d), 2-chloroadenosine (CADO, the stable analogue of adenosine, 2 mg/kg/d), GGD (5.4 g/kg/d) and GGD (5.4 g/kg/d) + CGS15943 (a nonselective adenosine receptor antagonist, 4 mg/kg/d). In vitro experiments, primary neonatal rat cardiomyocytes (NRCM) were divided into Con, PE (100 µM), CADO (5 µM), GGD (10−5 g/mL) and GGD (10−5 g/mL) + CGS15943 (5 µM). Ultrasound, H&E and Masson staining, hypertrophic genes expression and cell surface area were conducted to verify the GGD efficacy. Adenosine receptors (ADORs) expression were tested via real-time polymerase chain reaction (PCR), western blotting and immunofluorescence analysis.Results Network pharmacology identified ADORs among those of the core targets of GGD. In vitro experiments demonstrated that GGD attenuated PE-induced increased surface area (with an EC50 of 5.484 × 10−6 g/mL). In vivo data shown that GGD attenuated PE-induced ventricular wall thickening. In vitro and in vivo data indicated that GGD alleviated PE-induced hypertrophic gene expression (e.g., ANP, BNP and MYH7/MYH6), A1AR over-expression and A2aAR down-expression. Moreover, CADO exerts effects similar to GGD, whereas CGS15943 eliminated most effects of GGD.Discussion and conclusions Our findings suggest the mechanism by which GGD inhibits cardiac hypertrophy, highlighting regulation of ADORs as a potential therapeutic strategy for HF.